Icy Cream 'Oo' Enterprise / Miguel Eswart Umpit ... [et al.] - Umpit, Miguel Eswart; Ismail, Sharul Nizam; Awang Bair, Anati; Rajin, Aiza Juraizah (2009)
We are starting our own business as partners, and all of us decided to call our business as Fried Ice Cream. Our main activity of business is introduced new flavor of Ice Cream instead of the original one. There are several departments in our business which are administrative department, operational department, marketing department and financial department. Each of us heads the department while one person acts as the General Manager, which heads all the departments in our business. We started this business by applying for loan and each of partners been approved for having with the amount of RM30, 000.00.